The use of podcast media as an innovative practice in higher education (Research, Society and Development, 2020)
It is believed that the development of new technologies based on creativity, autonomy and critical reflection favors the act of educating students of the 21st century who are being greatly impacted by the VUCA world, an acronym for Volatility, Uncertainty, Complexity and Ambiguity. After conducting the studies, it was possible to answer the research problem, since it is possible to take advantage of the podcast to enhance the teaching / learning process. Hypotheses 1 and 2 were confirmed by the fact that the podcast has the capacity to enhance the dissemination of knowledge, stimulate the autonomy of studies in the search for protagonism, and can be explored at different levels of education. The objective was also achieved with a view to ratifying that the use of podcast media makes, in fact, the teaching practice innovative in higher education, as long as the teacher plays the role of mediating, questioning and guiding in order to promote the development and learning of the student. Exploratory research was carried out. As for the procedures, the research was of the bibliographic and experimental type through a quantitative approach with the application of a questionnaire carried out through Google Forms, and qualitative with the use of open questions for students' suggestions. As a contribution, the authors suggest to continue the research, with the intention of verifying whether the use of the podcast in the period of the pandemic of COVID-19, potentiated the construction of knowledge and, if in this challenging period, the tool made the class more attractive and collaborative.